Escória de metalurgia como corretivo de acidez do solo e fonte de nutrientes para arroz e soja - Silva, Gabrielly Nayara Tavares da (2021)
Brazilian soils are highly weathered, have low natural fertility and high acidity. Thus, the practice of liming is essential for the management of these soils to achieve high crop productivity. Slags are by-products generated in great amounts during the production of steel and metal alloys. These by-products may have potential to amend soil acidity since they contain Ca and Mg silicates and oxides. Therefore, slag appears as a sustainable source to be used as an acidity amendment in Brazilian soils and as a source of Ca and Mg for plants. However, before being used for this purpose, studies must be carried out to assess its agronomic efficiency. Therefore, the objective of this work was to study the potential use of a metallurgical slag, in comparison with a commercial limestone, as an acidity amendment in two contrasting Brazilian soils and as a source of nutrients for the cultivation of rice and soybean. For this, pot studies were carried out in a greenhouse, with the slag and commercial limestone being previously applied to the soils (medium and clayey texture) in two doses, to increase the base saturation to 50 and 100%. Considering that each crop was treated as an experiment and that, within each experiment, the soils were evaluated separately, the experimental design in each situation was the completely randomized block, consisting of 2 products x 2 doses + 1 control for each type of soil, totaling 40 pots per crop (4 replicates of each treatment). The fertilization was carried out with N, P, K, S, B, Cu, Mo, and Zn at doses of 300, 200, 150, 50, 0.5, 1.5, 0.1, and 5 mg dm-3 respectively. For rice, 10 seeds were sown and 3 seeds per pot were left after emergence, whereas for soybeans, 5 seeds were sown and 2 seeds per pot were left after emergence. The experiment was carried out until the final stage of the crop maturation, in which chemical analyzes were carried out on plants (roots, shoots, and grains), as well as in the soil after the crop cultivation. The slag showed chemical and physical characteristics within the limits required by current legislation for soil acidity amendments. Slag was as efficient as limestone in increasing soil pH and decreasing Al3+ saturation at the lowest dose applied to both soils cultivated with rice and soybean. Furthermore, the slag was able to supply Ca and Mg to rice and soybean plants, similarly to what was verified for commercial limestone.